PEMENUHAN HAK ASASI MANUSIA OLEH PEMERINTAH KOTA BUKITTINGGI TERHADAP PEDAGANG KAKI LIMA PRESPEKTIF SIYASAH DUSTURIYAH - Yana Syukra; Emrizal Emrizal; Roni Efendi (Institut Agama Islam Negeri Batusangkar, 2022)
This study examines the Fulfillment of Human Rights by the City Government of Bukittinggi on Human Rights. Review of Siyasah Dustiriyah. The problem is how to fulfill the human rights of street vendors (hereinafter written as PKL) by the City Government of Bukittinggi, and how to review the dusturiyah siyasa of the fulfillment of human rights to street vendors. This research is a type of empirical juridical research or field (field research). The sources of this research consist of primary data sources, namely the Head of the Legal Division in Bukittinggi City, the Civil Service Police Unit (hereinafter written as SATPOL PP) Bukittinggi City, street vendors and secondary data, namely scientific books, research results and related legislation. with research. Data collection techniques are interviews and documentation. After the data was obtained, then the data were analyzed using a qualitative descriptive method. To ensure the validity of the data, a data credibility test was used which was carried out through triangulation. Efforts to fulfill the human rights of street vendors by the Bukittinggi City Government have been carried out, the first such as facilitating a place to sell for street vendors, such as the kiosks that have been built by the Bukittinggi City Government, precisely in a row of roads located in the Aua Tajungkang Village, Tangah Sawah District, Guguak Panjang City. In Bukittinggi, the two street vendors are required to pay the rental fee for the kiosk they occupy every month to the Bukittinggi City Market Service Office, then for street vendors who are still selling in places that are not designated for them to trade, they will be given sanctions, such as verbal warnings by the Satpol PP. Siyasah dusturiyah explains the making of laws and regulations, where the concept explains the application of Islamic law to obey the rules that have been made by the government. In the city of Bukttinggi, the Government has issued Regional Regulation Number 8 of 2014 concerning the Arrangement and Empowerment of Street Vendors. As the Regional Regulation has not been able to fully cover the fulfillment of human rights, so it seems that the Government has not provided fulfillment and justice to street vendors and the actions taken by law enforcement officers who have not been corrected in carrying out their duties.